Pengaruh Dosis, pH, dan Waktu Pengendapan dalam Penyisihan TSS dan COD pada Air Limbah Kantin Menggunakan Biokoagulan Kulit Jeruk - Marsanda Amelia Putri; Munawar Ali; Praditya Sigit Ardisty Sitogasa (Jurnal Serambi Engineering, 2025)
Canteen wastewater is a type of domestic effluent generated from cooking and dishwashing activities, typically containing high levels of organic matter such as fats, oils, food residues, and key pollutants like Total Suspended Solids (TSS) also Chemical Oxygen Demand (COD). This study evaluates the effectiveness of sweet orange peel (Citrus sinensis)-based bio-coagulant in removing TSS also COD from canteen wastewater. Orange peel was selected due to its bioactive compounds like a pectin, flavonoids, also organic acids, that contain hydroxyl and carboxyl functional groups vital for coagulation-flocculation processes. Treatment was conducted using the jar test method with variations in pH, dosage, and settling time. The results showed that the optimum condition was achieved at pH 3, a dosage of 2 g/L, also a settling time of 45 minutes, resulting in TSS removal efficiency of 30.48% and COD removal of 29.29%. These findings confirm the potential of orange peel as an eco-friendly natural coagulant for canteen wastewater treatment.